Evaluation of Pediatricians' Perspectives on the Nutrition of Premature Infants - Mustafa Şenol AKIN; Mustafa Törehan ASLAN; İbrahim Murat HİRFANOĞLU; Fuat Emre CANPOLAT (Forbes Tıp Dergisi)
Objective: Nutrition is essential in managing premature infants, as proper practices reduce morbidity and mortality risks. Pediatricians must be knowledgeable and effectively implement nutrition guidelines for premature infants both in the neonatal intensive care unit (NICU) and post-discharge. This study aims to evaluate pediatricians' perspectives in Türkiye on the nutrition of premature infants. Methods: Conducted from August to September 2024, this cross-sectional study surveyed pediatricians across various Turkish provinces and hospitals about their views on premature infant nutrition. Following ethical approval, a questionnaire assessed their opinions on feeding practices in the NICU and after discharge. Results: Of the participating physicians, 72% worked in private hospitals, and 28% in state hospitals. Sixty-two percent had over three years of NICU experience, with all seeing at least 1-3 premature infants daily. Among respondents, 93% supported using breast milk fortifiers alongside breast milk for NICU patients, while 7% preferred exclusive breast milk. The main factor affecting adherence to NICU nutrition protocols was the ease of product availability. After discharge, 97% of physicians recommended formula for premature infants. Conclusion: Premature infant nutrition is vital for ensuring a healthy outcome and reducing complications. Although neonatologists primarily focus on this area, pediatricians' practices and knowledge are also significant. Our findings indicate that most pediatricians demonstrate appropriate knowledge and practices regarding premature infant nutrition.